A dialética da gênese do empréstimo na constituição de psicolingüística - Maia, Eleonora Albano da Mota (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
This paper attempts to demonstrate thet, in spite os its prestige as an independent academic field, psycholinguistics is still struggling for epistemological autonomy from linguistics and psychology. The reason is that all current questions in the field spring from two opposing tendencies that have played alternating roles in its historical development. One is to borrow theory and method from both linguistics and psychology. The other is to put a premium on genetic issues and thereby attempt to reconstruct the field anew. It is argued that recognition of the dialectical nature of the relationship between these two tendencies would clarify important epistemological issues and thus contribute to the advancement of the field.